Patterns of spinal motion, kinematic spaces and the land-to-sea transition in carnivorans - Esteban, Juan Miguel; Martín-Serra, Alberto; Pérez-Ramos, Alejandro; Figueirido-Castillo, Francisco Borja (Wiley, 2025)
The vertebral column of pinnipeds (seals and kin) has undergone profound morphological changes, yet the functional consequences of these changes remain poorly explored. Here, we quantify the osteological range of motion (oROM) of presacral intervertebral joints across the cervical, thoracic, and lumbar regions of pinnipeds, as well as terrestrial and semi-aquatic carnivores for comparative purposes. To do this, we used 3D reconstructions of vertebral columns, and we applied Autobend, an experimentally validated methodology to quantify intervertebral joint mobility across axial, lateral, and sagittal planes from dry vertebrae. Our results reveal that pinnipeds exhibit greater intervertebral mobility than non-aquatic taxa, particularly in the lumbar region, which probably relates to their aquatic adaptations. However, cervical mobility is more reduced in pinnipeds, likely due to decreased reliance on head maneuverability. We also demonstrate differences among pinniped families that may relate to their distinct swimming styles and locomotion on land. Accordingly, the spine of otariids retains higher flexibility, while that of phocids exhibits greater coordination and rigidity across the thoracic region but high mobility in the lumbar spine. Odobenids show a unique pattern with reduced cervical mobility but high thoracic and lumbar flexibility. Finally, we relate these kinematic patterns to previously published data on vertebral integration and modularity. Our results may agree with previous hypotheses that reduced morphological integration is associated with increased mobility and vice versa.
Keywords: Pinnípedos; Columna vertebral; Aquatic adaptations; Fissipeds; Mobility; Pinnipeds; Vertebrae